The Diagnosis of Hypersensitivity Pneumonitis and the Role of Lung Biopsy. Issue 6 (30th November 2020) - Seixas, Eduarda; Serra, Paula; Aguiar, Renata; Ferreira, Margarida; Ferreira, Pedro Gonçalo
Abstract : Hypersensitivity pneumonitis (HP) refers to a collective noun of diffuse lung diseases encompassing some degree of bronchiolar and interstitial granulomatous inflammation that results from persistent inhalation exposure and consequent immune sensitization to a large potential diversity of (predominantly) organic antigens in predisposed individuals. In suspected cases of HP, forceps transbronchial lung biopsy (TBLB) has been traditionally performed on a case-by-case basis along with bronchoalveolar lavage. This option has been subject to some debate and its use is more restrained in the presence of a chronic fibrotic form of HP—where surgical lung biopsy is classically recommended in the face of the need for a more reliable differentiation from fibrotic idiopathic interstitial pneumonias. We intended to assess the diagnostic contribution of conventional TBLB in the combined multidisciplinary diagnosis of an HP patient cohort. A retrospective evaluation of all the diagnostic elements and level of confidence from all HP cases followed in an interstitial lung disease ILD outpatient clinic of a district hospital center (Centro Hospitalar do Baixo Vouga), from June 2015 to August 2019, and simultaneously evaluated in a multidisciplinary team discussion of the same hospital, comprising an interstitial lung disease dedicated lung physician, a chest radiologist, 2 rheumatologists, and a pathologist. We identified 78 patients (mean age: 70.5 y, interquartile range: 58.5 to 78.0) with a slight female predominance. Most of the patients (61.5%) had chronic/fibrotic HP. The most frequently identified inducing antigens were avian antigens in 59.0% of cases, followed by molds in 20.5%. Of the 72 patients who underwent bronchofibroscopy, 36.1% (n=26) conventional TBLB performed, predominantly in the segments of the right lower lobe with an average number of 3.9 biopsies (SD±1.4) accomplished per patient. In 50.0% of the cases submitted to TBLB, the biopsies showed representative material with histologic features (definite or supportive) which had some degree of contribution for the diagnostic discussion. Among the patients where TBLBs were not performed or whose results were found to be devoid of significant findings, 73.1% were still diagnosed as HP without the need for surgical video-assisted thoracoscopic lung biopsy/transbronchial lung cryobiopsy (VATS/TBLCB) on the grounds of other diagnostic elements; 15.4% of patients were diagnosed with HP after a VATS/TBLCB procedure. Lastly, around 11.5% of patients were considered to have an unacceptable risk for VATS/TBLCB but, on the basis of clinical, radiologic, and immunologic elements received a multidisciplinary provisional diagnosis still with a reasonable level of confidence. Regarding complications with TBLB, there were 2 cases of moderate bleeding (7.6%) and 1 pneumothorax (3.8%) that did not require drainage. Notwithstanding its limitations, TBLB can still have a role in the diagnostic workup of HP, namely in acute/inflammatory HP, adding definite or supportive histologic information for multidisciplinary discussion in up to 50% of cases. TBLB can augment diagnostic yield at the expense of only a minimal increase of risk, as it is a universally available technique that can be performed along with bronchoalveolar lavage. This has important implications, particularly in centers devoid of TBLCB, as a surgical biopsy can be avoided in approximately half of patients who are eventually diagnosed with HP.